Soluble diazaiptycenes: materials for solution-processed organic electronics - Biegger, Philipp; Stolz, Sebastian; Intorp, Sebastian; Zhang, Yexiang; Engelhart, Jens U.; Rominger, Frank; Hardcastle, Kenneth I.; Lemmer, Uli; Qian, Xuhong; Hamburger, Manuel; Bunz, Uwe H. F. (The journal of organic chemistry, 2015)
The synthesis and characterization of soluble azaiptycenes is reported. Optical and physical properties were studied and compared with those of the structurally consanguine azaacenes. Electrochemical experiments and quantum-chemical calculations revealed the electronic structure of the iptycene derivatives. Their crystallization behavior was examined. A highly fluorescent amorphous diazatetracene derivative was integrated into a simple organic light-emitting diode, showing enhanced performance compared with that of previously reported, structurally similar tetracenes.